Mengoptimalisasikan Kinerja Unit Riset dan Pengembangan di Perusahaan PT Kimia Farma (Persero), Tbk. melalui Penyempurnaan Struktur Organisasi Dalam Menghadapi Persaingan di Era Globalisasi dan Asean-China Free Trade Area (A-CFTA) - Nurgraha, Rd.Much.Jusup (Universitas Brawijaya, Indonesia, 2014)
In globalization era and A-CFTA competition are getting tighter, in order to survive PT Kimia Farma (persero) must be synchronized of working plan between research and development department with marketing department. The improvement of organization structure must be done in order to compete the changing of competitive atmosphere through the direction improvement, objectives, business process to be more effective and efficient. In addition, the improvement of workers'quality is based on job analysis through competency improvement. The respondents are chosen through the consideration of their direct contribution on business activity process by using interview, observation, and survey method. The researcher arranges the improvement through developing of organization structure, developing business process, arranging job analysis based on competency business process, designing the improvement of organization structure based on business process and job analysis in whish has competencies in research and development department. The results of this study are the improvement of vision, mission, objective, organization value, business process by making a proposal for new products, job analysis by adding some competencies. From this improvement arrangement shows that organization not only department based on function but also department based on product and function using decentralization system.